Global 1968: Implications for Adult Education in Social Movements - Maria A Vetter (Adult Education Research Conference, 2019)
May 2018 marked the fiftieth anniversary of one of the most revolutionary moments of the 20th Century. We will address the pedagogical aspects of the movements around the world.
Keywords: 1968; Social Movements; Adult Education; China; Americas